Physical Education and Sport: Facing Change (Fiep Bulletin - online, 2014)
Profession dialogue and co-operation among experts in physical education and sport and professionals in other areas of society-education, health, culture, sciences, economics, politics etc. - are the key elements for facing change. Multidisciplinary collaboration allows for comprehensive identification of current issues and the differentiated description of status on the national and international levels. Such analyses from various disciplinary/societal perspectives can serve as a basis for portraying future scenarios: Will physical education - due to progressing marginalisation - disappear from the school curriculum? Will billions of people access sport events on the Internet instead of watching sport "live" or practising sport themselves? Will we soon have a health revolution? Shaping the future of physical education and sport requires vision, a mission, values, goals, and strategies. International events such as the World summit on Physical Education win the Berlin Agenda for Action for Government Ministers, and MINEPS III with the Declaration of Punta del Este, are promising initiative on the worlds scale. These initiatives are clear indication for a will to face change. However, joint effects on national, regional and international levels- both by governments and non-governmental organisations - are necessary to move toward effective implementation. A permanent monitoring and quality control system needs to be in place, accompanied by bridge-building and networking initiatives.